A LITERARY AND MYSTICAL ANALYSIS OF HOFIZ KHOREZMI'S GHAZAL: SYMBOLISM, SUFISM, AND SPIRITUAL YEARNING - Maksudova Nigina Umar kizi (Modern American Journals, 2025)
This study explores the mystical and poetic depth of a ghazal by Hofiz Khorezmi, a notable figure in 14th-century Central Asian literature. Through a detailed linguistic, stylistic, and conceptual analysis, the article investigates how the poet blends traditional Sufi metaphysics with classical poetic symbolism. Each bayt (couplet) is examined for its structural integrity and spiritual nuance, revealing recurrent motifs of divine love, existential sorrow, annihilation of the self (fanā), and longing for union with the Divine. The ghazal’s metaphorical lexicon—including imagery of the nightingale (bulbul), the rose garden (guluzor), and the beloved’s tresses (zulf)—is contextualized within both Persian and Turkic literary traditions. The study concludes that Hofiz Khorezmi’s poetry exemplifies a synthesis of devotional intensity and refined classical aesthetics, positioning him among the key transmitters of mystical thought through verse. This article contributes to a deeper understanding of the intersection between poetics and spiritual philosophy in medieval Islamic literary culture.
Keywords: Hofiz Khorezmi, sufi literature, classical turkic poetry, mystical ghazal, fanā (annihilation in divine love), poetic symbolism, metaphysical longing, nightingale and rose imagery, persianate literary tradition, islamic spiritual poetics